Analisis Hubungan Kondisi Gudang terhadap Tidak Berjalannya Prinsip 5S di PT. Yasunli Abadi Utama Plastik - M Hudori; Sylvia Madusari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
PT Yasunli Utama Abadi Plastik is a manufacturing company engaged in the plastics injection. The company has a finished goods warehouse as part responsible for controlling the products. Currently the problem that occurred in the warehouse is not the passage of the working principles of 5S is on stage Seiketsu and Shitsuke. This study aims to determine the cause of the ineffectiveness of the 5S principles, determine the relationship between the condition of the warehouse that are not compliant with any of the activities of the warehouse, as well as showing losses incurred when the 5S principles are not going well. Analysis was conducted on the causes and consequences of problems that occur. After finding the causes and consequences of these problems will be tested on the relationship between the causes with their effects, as well as prove any harm to the company if the principles of 5S is not going well. The results showed that the factors causing the ineffectiveness of 5S principles are human and there is a relationship which had a negative impact among warehouse conditions incompatible with the standard warehouse activities, so that the company suffered losses during the 5S principles are not going well.